An econometric model for resource management in competitive wireless data networks. - Das, S.K.
This article investigates the role and importance of the economic aspects that are vital to the success of wireless services deployment and provider selection by users in a competitive environment. We show how some of the econometric measures can meaningfully capture the user decisions/actions (e.g., churning) that can potentially be utilized by the providers in managing radio resources (e.g., bandwidth) in wireless data networks. In particular, by modeling the interaction between a service provider and its customers (or users) as a non-cooperative game, we propose a novel cross-layer resource management framework for integrated admission and rate control in CDMA networks. Analytical and simulation results demonstrate how the proposed framework can help minimize customer churning and maximize revenue for the wireless operators, yet optimizing customer satisfaction by providing differentiated quality of service to different classes of users.
Keywords: CDMA network; Code division multiple access; Cross-layer resource management framework; Differentiated quality of service; Econometric model; Wireless data network; Wireless services deployment